2021
DOI: 10.1055/a-1553-3265
|View full text |Cite
|
Sign up to set email alerts
|

Astaxanthin Induces the Expression of CatSper1 Gene and Protects Sperms in Toxicity Induced by Cadmium in Mice

Abstract: Cadmium (Cd) as a heavy metal damages testis and decreases fertility, however, antioxidants can improve sperm parameters and decrease male infertility. In this study we investigated the effect of astaxanthin (AST) on sperm parameters, expression levels of CatSper1 and CatSper2 genes in presence of Cd in mice. Thirty adults’ mice were divided into 4 groups, sham group received olive oil and saline (olive oil is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Compatible with another study on mice sperm viability, normal morphology, motility index, and antioxidant enzyme activities (T-AOC) were higher in our study due to CatSper1 and CatSper2 gene expression. Conversely, DNA damage and oxidative stress induced by lipid peroxidation (MDA) was significantly lower in our study [48]. Another study in mice demonstrated that AXT significantly restored sperm DNA damage caused by cyclophosphamide testicular toxicity confirmed by histological examination [20].…”
Section: Discussionmentioning
confidence: 41%
“…Compatible with another study on mice sperm viability, normal morphology, motility index, and antioxidant enzyme activities (T-AOC) were higher in our study due to CatSper1 and CatSper2 gene expression. Conversely, DNA damage and oxidative stress induced by lipid peroxidation (MDA) was significantly lower in our study [48]. Another study in mice demonstrated that AXT significantly restored sperm DNA damage caused by cyclophosphamide testicular toxicity confirmed by histological examination [20].…”
Section: Discussionmentioning
confidence: 41%
“…Free radical scavenging (chain-terminating) antioxidants, such as vitamins E and C, are chemicals with large resonance-stabilized electron clouds that work as electron donors [204] and vitamin C works through the activation of biological antioxidant defenses, such as GSH-linked enzymes [205,206]. Astaxanthin also prevents oxidative stress induced by cadmium [207], copper [208], and cobalt [209] and alleviates cell damage caused by these metals. Selenium [210], and lycopene [211] have been reported as antioxidants against the toxicity of heavy metals, such as cadmium, lead, and chromium.…”
Section: Stoichiometric Antioxidantsmentioning
confidence: 99%